Nano high-entropy phosphide / carbon composite material and preparation method thereof
By using phosphorus-containing resin to prepare nano-high entropy phosphide/carbon composites, the problems of complex and high cost of synthesis of existing high entropy materials are solved, and the preparation of nano-level high-efficiency electrocatalytic materials is realized, with the advantages of low cost, easy operation and high efficiency catalysis.
Patent Information
- Application Number
- CN202411681311.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-11-22
AI Technical Summary
The synthesis process of existing high-entropy materials is complex, costly and large in size, making it difficult to prepare high-efficiency electrocatalytic materials at the nano-level.
The nano-high entropy phosphide/carbon composite material is prepared by using phosphorus-containing resin as raw material, and the pH value is adjusted by acid solution, vacuum suction filtration and heat treatment, achieving the controllability of nano-level particle size and composition.
The preparation of nano high-entropy phosphide/carbon composite materials with low cost, easy to operate and green and environmentally friendly has high efficiency and stable catalytic properties, and is suitable for electrocatalytic sulfur reduction reactions and lithium-sulfur battery positive electrode catalysts.
Smart Images

Figure CN119565647A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a preparation method of a phosphide / carbon composite material, and in particular to a nano high entropy phosphide / carbon composite material and a preparation method thereof. Background Art
[0002] Single-component electrocatalysts, such as metal oxides and metal sulfides, show limited catalytic activity in electrocatalytic processes due to their simple components and structures. In recent years, single-phase multi-component high-entropy materials, which have multiple metal active centers and structural disorder, have shown significant catalytic activity and fast redox reaction kinetics. Among them, high-entropy alloys, high-entropy oxides, and high-entropy sulfides have been widely used in fields such as electrochemical energy storage and catalysis. However, the current synthesis process of high-entropy materials is complex, costly, and easy to agglomerate, and the prepared high-entropy materials are often irregular block morphologies of micrometers or even larger sizes. Therefore, it remains a challenge to develop a simple and efficient preparation method to synthesize nanoscale high-entropy materials.
[0003] The phosphorus element in transition metal phosphides has metallic properties that can adjust the electronic structure of phosphides, so phosphides usually exhibit metal-like properties and efficient catalytic activity. In order to further optimize the composition and structure of phosphides, thereby improving the catalytic activity of redox reactions, the synthesis of high-entropy phosphides is a challenging and meaningful strategy. At present, the synthesis methods of high-entropy phosphides mainly include eutectic solvent method, hydrothermal / solvothermal method, sol-gel method and high-temperature solid phase method, and even require a combination of multiple methods. Usually, these high-entropy phosphides have large particle sizes and need to be further loaded on carbon-based materials to meet the needs of electrocatalysts. Therefore, it is of great research value and economic benefit to develop a low-cost, easy-to-operate and large-scale production method to synthesize nano high-entropy phosphide / carbon composite materials in one step for use as efficient electrocatalytic materials. Summary of the invention
[0004] Based on the deficiencies of the prior art, the present invention provides a nano high-entropy phosphide / carbon composite material and a preparation method thereof, which adopts relatively cheap raw materials to obtain a low-cost, easy-to-operate, green and environmentally friendly nano high-entropy phosphide particle with nanometer size and controllable composition and is evenly distributed in the layered porous carbon.
[0005] To achieve the above purpose, the technical solution provided by the present invention is as follows:
[0006] A nano high entropy phosphide / carbon composite material, the general formula of the nano high entropy phosphide / carbon composite material is Nano-(Fe a Co b Ni c Cu d Mo e)2P / C, wherein the subscript value ranges are a is 0.25-0.3, b is 0.25, c is 0.25, d is 0.1-0.13, and e is 0.1-0.12; the nano high entropy phosphide / carbon composite material has efficient and stable catalytic performance.
[0007] The method for preparing the nano high entropy phosphide / carbon composite material as described above comprises the following steps:
[0008] (1) soaking the phosphorus-containing resin in an acid solution to adjust the pH of the phosphorus-containing resin, vacuum filtering, drying, and then crushing;
[0009] (2) The phosphorus-containing resin obtained after pulverization in step (1) is placed in a beaker, and then deionized water is added and stirred to obtain a mixture. The Fe salt, Co salt, Ni salt, Cu salt and Mo salt solutions are mixed evenly and added to the mixture. The mixture is magnetically stirred at a constant temperature, vacuum filtered and dried to obtain a precursor resin containing five elements of Fe, Co, Ni, Cu and Mo, which is recorded as M + Resin;
[0010] (3) The M obtained in step (2) + The resin is placed in a mortar, alkaline substances are added and ground sufficiently, and a heat treatment is performed under protective gas. After the reaction is completed, the resin is naturally cooled. The heat-treated material is washed with deionized water until it is neutral and dried to obtain a nano high entropy phosphide / carbon composite material.
[0011] Preferably, the phosphorus-containing resin in step (1) is LXP-P01 type resin.
[0012] Preferably, the acid solution in step (1) is one of hydrochloric acid solution, nitric acid solution or acetic acid solution; and the concentration of the acid solution is 0.5 to 2.5 mol / L.
[0013] Preferably, the pH value in step (1) is adjusted to 5 to 7, preferably 6; after vacuum filtration, the mixture is dried at 60° C. until the moisture content does not exceed 8 wt % and then crushed.
[0014] Preferably, in step (2), 5 mL of deionized water is added per gram of phosphorus-containing resin.
[0015] Preferably, the Fe salt, Co salt, Ni salt, Cu salt and Mo salt solution described in step (2) are each added in an amount of 50 mL; the Fe salt is ferric chloride (FeCl3) with a concentration of 0.2 to 0.6 mol / L, preferably 0.6 mol / L; the Co salt is cobalt chloride (CoCl2) with a concentration of 0.2 to 0.6 mol / L, preferably 0.5 mol / L; the Ni salt is nickel chloride (NiCl2) with a concentration of 0.2 to 0.6 mol / L, preferably 0.5 mol / L; the Cu salt is cupric chloride (CuCl2) with a concentration of 0.2 to 0.6 mol / L, preferably 0.2 mol / L; the Mo salt is molybdenum pentachloride (MoCl5) with a concentration of 0.2 to 0.6 mol / L, preferably 0.2 mol / L.
[0016] Preferably, the vacuum filtration in step (2) is followed by complete drying at 60°C; and the drying in step (3) is complete drying at 60°C.
[0017] Preferably, the constant temperature magnetic stirring in step (2) is to maintain the temperature at 50-65°C, the stirring rate at 300 rpm, and stir for 3-6 hours; preferably, stirring at 55°C and 300 rpm for 4 hours.
[0018] Preferably, the alkaline substance described in step (3) is one of potassium hydroxide or sodium hydroxide, preferably potassium hydroxide; the protective gas described in step (3) is N2 or Ar atmosphere; the protective gas is preferably N2.
[0019] Preferably, in step (3), M + The amount of resin added is 1 to 3 g; M + The preferred amount of resin added is 2 g; + The mass ratio of the resin to the alkaline substance is 1:0.05-0.4 (preferably 1:0.25-0.4).
[0020] Preferably, the one-step heat treatment in step (3) is: heating to 750-1050°C at a heating rate of 5-10°C / min and keeping warm for 1-3h; the heating rate is preferably 5°C / min; and the keeping warm time is preferably 1h.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] The method of the invention adopts phosphorus-containing resin as raw material, and the resin adopted is green and environmentally friendly, low in price, and low in raw material and preparation cost; the method of the invention is simple to operate, and the particle size of the prepared nano high entropy phosphide / carbon composite material reaches nanometer level, and the particle size is controllable; the nano high entropy phosphide / carbon composite material Nano-(Fe a Co b Ni cCu d Mo e )2P / C exhibits excellent catalytic ability in the electrocatalytic sulfur reduction reaction; Nano-(Fe a Co b Ni c Cu d Mo e )2P / C shows stable and efficient electrocatalytic activity as a cathode catalyst for lithium-sulfur batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 The nano high entropy phosphide / carbon composite material Nano-(Fe 0.30 Co 0.25 Ni 0.25 Cu 0.10 Mo 0.10 )SEM photograph of 2P / C.
[0024] Figure 2 The nano high entropy phosphide / carbon composite material Nano-(Fe 0.30 Co 0.25 Ni 0.25 Cu 0.10 Mo 0.10 )EDS photo of 2P / C.
[0025] Figure 3 The nano high entropy phosphide / carbon composite material Nano-(Fe 0.30 Co 0.25 Ni 0.25 Cu 0.10 Mo 0.10 )LSV performance curve of S8 reduction of 2P / C.
[0026] Figure 4 The nano high entropy phosphide / carbon composite material Nano-(Fe 0.30 Co 0.25 Ni 0.25 Cu 0.10 Mo 0.10 )LSV performance curve of hydrogen evolution reaction (HER) of 2P / C.
[0027] Figure 5 The nano high entropy phosphide / carbon composite material Nano-(Fe 0.30 Co 0.25 Ni 0.25 Cu 0.10 Mo 0.10)2P / C electrochemical cycle performance curve of positive electrode catalyst applied to lithium-sulfur battery.
[0028] Figure 6 The nano high entropy phosphide / carbon composite material Nano-(Fe 0.30 Co 0.25 Ni 0.25 Cu 0.10 Mo 0.10 )SEM image of 2P / C.
[0029] Figure 7 The nano high entropy phosphide / carbon composite material Nano-(Fe 0.30 Co 0.25 Ni 0.25 Cu 0.10 Mo 0.10 )LSV performance curve of S8 reduction of 2P / C.
[0030] Figure 8 The nano high entropy phosphide / carbon composite material Nano-(Fe 0.30 Co 0.25 Ni 0.25 Cu 0.10 Mo 0.10 ) LSV performance curve of HER of 2P / C. DETAILED DESCRIPTION
[0031] The specific embodiments are described in detail below in conjunction with the accompanying drawings, but it should be understood that the scope of protection of the present invention is not limited by the specific embodiments. The raw materials and reagents used in the examples are all commercially available unless otherwise specified. The phosphorus-containing resin used in the examples is purchased from the resin LXP-P01 produced by Xi'an Sunresin Technology Co., Ltd. (Sunresin Technology).
[0032] Example 1
[0033] A method for preparing a nano high entropy phosphide / carbon composite material, the operating steps are as follows:
[0034] (1) 300 g of phosphorus-containing resin was immersed in a 0.5 mol / L nitric acid solution to adjust the pH value of the resin to 6, and then vacuum filtered and dried at 60° C. until the water content did not exceed 8 wt %, and then ground in a grinder;
[0035] (2) 20 g of the phosphorus-containing resin obtained after crushing in step (1) was placed in a beaker, and then 100 mL of deionized water was added and stirred to obtain a mixture; a FeCl3·6H2O solution with a concentration of 0.6 mol / L and a volume of 50 mL, a CoCl2·6H2O solution with a concentration of 0.5 mol / L and a volume of 50 mL, a NiCl2·6H2O solution with a concentration of 0.5 mol / L and a volume of 50 mL, a CuCl2·2H2O solution with a concentration of 0.2 mol / L and a volume of 50 mL, and a MoCl5 solution with a concentration of 0.2 mol / L and a volume of 50 mL were mixed and added to the above obtained mixture, and the temperature was maintained at 55° C. and the stirring rate was 300 rpm. Constant temperature magnetic stirring was performed for 4 h, and after vacuum filtration, it was completely dried at 60° C. to obtain a precursor resin containing five metal elements of Fe, Co, Ni, Cu and Mo, which was recorded as M + Resin;
[0036] (3) Take the M obtained in step (2) + 2g of resin was placed in a mortar and + The mass ratio of resin to potassium hydroxide was 1:0.4, 0.8 g of potassium hydroxide was added, and the mixture was fully ground for 30 min. Then, the mixture was heated to 1000 °C at a heating rate of 5 °C / min in a N2 atmosphere and kept for 1 h for a one-step heat treatment. After the reaction was completed, the mixture was naturally cooled. The heat-treated substance was washed with deionized water until it was neutral, and then completely dried at 60 °C to obtain a nano high entropy phosphide / carbon composite material Nano-(Fe 0.30 Co 0.25 Ni 0.25 Cu 0.10 Mo 0.10 )2P / C.
[0037] Example 2
[0038] A method for preparing a nano high entropy phosphide / carbon composite material, the operating steps are as follows:
[0039] (1) 300 g of phosphorus-containing resin was immersed in a 0.5 mol / L nitric acid solution to adjust the pH value of the resin to 6, and after vacuum filtration, it was dried at 60° C. until the moisture content did not exceed 8%, and then crushed in a pulverizer;
[0040] (2) 20 g of the phosphorus-containing resin obtained after crushing in step (1) was placed in a beaker, and then 100 mL of deionized water was added and stirred to obtain a mixture. A FeCl3·6H2O solution with a concentration of 0.4 mol / L and a volume of 50 mL, a CoCl2·6H2O solution with a concentration of 0.4 mol / L and a volume of 50 mL, a NiCl2·6H2O solution with a concentration of 0.4 mol / L and a volume of 50 mL, a CuCl2·2H2O solution with a concentration of 0.2 mol / L and a volume of 50 mL, and a MoCl5 solution with a concentration of 0.2 mol / L and a volume of 50 mL were mixed and added to the mixture, and the temperature was maintained at 55° C. and the stirring rate was 300 rpm. Constant temperature magnetic stirring was performed for 4 h, and after vacuum filtration, it was completely dried at 60° C. to obtain a precursor resin containing five metal elements of Fe, Co, Ni, Cu and Mo, which was recorded as M + Resin;
[0041] (3) Take the M obtained in step (2) + 2g of resin was placed in a mortar and + The mass ratio of resin to potassium hydroxide was 1:0.3, 0.6 g of potassium hydroxide was added, and the mixture was fully ground for 30 min. Then, the mixture was heated to 900 °C at a heating rate of 5 °C / min in a N2 atmosphere and kept for 1.5 h for a one-step heat treatment. After the reaction was completed, the mixture was naturally cooled. The heat-treated substance was washed with deionized water until neutral, and completely dried at 60 °C to obtain a nano high entropy phosphide / carbon composite material Nano-(Fe 0.25 Co 0.25 Ni 0.25 Cu 0.13 Mo 0.12 )2P / C
[0042] Example 3
[0043] A method for preparing a nano high entropy phosphide / carbon composite material, the operating steps are as follows:
[0044] (1) 300 g of phosphorus-containing resin was immersed in a 0.5 mol / L nitric acid solution to adjust the pH value of the resin to 7, vacuum filtered and dried at 60° C. until the moisture content did not exceed 8%, and then crushed in a pulverizer;
[0045] (2) 40 g of the phosphorus-containing resin obtained after crushing in step (1) was placed in a beaker, and then 100 mL of deionized water was added and stirred to obtain a mixture. A FeCl3·6H2O solution with a concentration of 0.6 mol / L and a volume of 50 mL, a CoCl2·6H2O solution with a concentration of 0.5 mol / L and a volume of 50 mL, a NiCl2·6H2O solution with a concentration of 0.5 mol / L and a volume of 50 mL, a CuCl2·2H2O solution with a concentration of 0.2 mol / L and a volume of 50 mL, and a MoCl5 solution with a concentration of 0.2 mol / L and a volume of 50 mL were mixed and added to the mixture, and the temperature was maintained at 65° C. and the stirring rate was 300 rpm. Constant temperature magnetic stirring was performed for 4 h, and after vacuum filtration, it was completely dried at 60° C. to obtain a precursor resin containing five metal elements of Fe, Co, Ni, Cu and Mo, which was recorded as M + Resin;
[0046] (3) Take the M obtained in step (2) + 1g of resin was placed in a mortar and + The mass ratio of resin to potassium hydroxide was 1:0.05, 0.05 g of potassium hydroxide was added, and the mixture was fully ground for 30 min. Then, the mixture was heated to 800 °C at a heating rate of 5 °C / min in a N2 atmosphere and kept at that temperature for 1.5 h for a one-step heat treatment. After the reaction was completed, the mixture was naturally cooled. The heat-treated substance was washed with deionized water until it was neutral, and then completely dried at 60 °C to obtain a nano high entropy phosphide / carbon composite material Nano-(Fe 0.30 Co 0.25 Ni 0.25 Cu 0.10 Mo 0.10 )2P / C.
[0047] Example 4
[0048] A method for preparing a nano high entropy phosphide / carbon composite material, the operating steps are as follows:
[0049] (1) 300 g of phosphorus-containing resin was soaked in a 0.5 mol / L nitric acid solution, the pH value was adjusted to 7, and the solution was filtered, dried, and then crushed;
[0050] (2) 30 g of the phosphorus-containing resin obtained after crushing in step (1) was placed in a beaker, and then 100 mL of deionized water was added and stirred to obtain a mixture. A FeCl3·6H2O solution with a concentration of 0.6 mol / L and a volume of 50 mL, a CoCl2·6H2O solution with a concentration of 0.5 mol / L and a volume of 50 mL, a NiCl2·6H2O solution with a concentration of 0.5 mol / L and a volume of 50 mL, a CuCl2·2H2O solution with a concentration of 0.2 mol / L and a volume of 50 mL, and a MoCl5 solution with a concentration of 0.2 mol / L and a volume of 50 mL were mixed and added to the mixture, and the temperature was maintained at 55° C. and the stirring rate was 300 rpm. Constant temperature magnetic stirring was performed for 5 h, and the mixture was filtered and dried to obtain a precursor resin containing five metal elements of Fe, Co, Ni, Cu and Mo, which was recorded as M + Resin;
[0051] (3) Take the M obtained in step (2) + 3g of resin was placed in a mortar and + The mass ratio of resin to sodium hydroxide was 1:0.2, 0.6 g of sodium hydroxide was added, and the mixture was fully ground for 30 min. Then, the mixture was heated to 1000 °C at a heating rate of 5 °C / min in a N2 atmosphere and kept for 1 h for a one-step heat treatment. After the reaction was completed, the mixture was naturally cooled. The heat-treated substance was washed with deionized water until it was neutral, and then completely dried at 60 °C to obtain a nano high entropy phosphide / carbon composite material Nano-(Fe 0.30 Co 0.25 Ni 0.25 Cu 0.10 Mo 0.10 )2P / C.
[0052] Comparative Example 1
[0053] A method for preparing a nano high entropy phosphide / carbon composite material, the operating steps are as follows:
[0054] (3) Take the M obtained in step (2) + 2g of resin was heated to 1000℃ at a heating rate of 5℃ / min in a N2 atmosphere and kept at this temperature for 1h for a one-step heat treatment. After the reaction was completed, it was naturally cooled. The material obtained after the heat treatment was washed with deionized water until it was neutral and completely dried at 60℃ to obtain a nano high entropy phosphide / carbon composite material Nano-(Fe 0.30 Co 0.25 Ni 0.25 Cu 0.10 Mo 0.10 )2P / C;
[0055] The remaining operations are the same as those in Example 1.
[0056] Figure 3-4 , Figure 7-8 Preparation of C that appears in:
[0057] Operation steps: (1) immerse 300 g of phosphorus-containing resin in a 0.5 mol / L nitric acid solution, adjust the pH value of the resin to 6, vacuum filter, dry at 60° C. until the moisture content does not exceed 8 wt%, and then grind in a grinder;
[0058] (2) 2 g of the phosphorus-containing resin obtained after pulverization in step (1) was placed in a mortar, 0.8 g of potassium hydroxide was added and fully ground for 30 min, and then the temperature was raised to 1000° C. at a heating rate of 5° C. / min under a N2 atmosphere and kept at that temperature for 1 h for a one-step heat treatment. After the reaction was completed, the mixture was naturally cooled, and the substance obtained after the heat treatment was washed with deionized water until it was neutral, and completely dried at 60° C. to obtain C for later use.
[0059] Performance Testing
[0060] 1. S8 reduction linear sweep voltammetry (LSV) test: 5 mg of the sample was ultrasonically dispersed and then dropped in the middle of the glassy carbon electrode. A mixture of 4 mM S8 and 1.0 M lithium bis(trifluoromethanesulfonyl)imide (LITFSI) dissolved in 1,2-dimethoxyethane (DME) and 1,3-dioxolane (DOL) solvent in a volume ratio of 1:1 was used as the electrolyte. The electrocatalytic sulfur reduction ability of the catalyst was tested on an electrochemical workstation. The samples tested were the nano high entropy phosphide / carbon composite material Nano-(Fe 0.30 Co 0.25 Ni 0.25 Cu 0.10 Mo 0.10 )2P / C, the above-mentioned spare C, the nano high entropy phosphide / carbon composite material Nano-(Fe 0.30 Co 0.25 Ni 0.25 Cu 0.10 Mo 0.10 )2P / C.
[0061] 2. Hydrogen evolution reaction (HER) linear sweep voltammetry (LSV) test: Before the test, H2 was passed for 30 minutes to saturate the solution, and H2 was continuously passed during the test to ensure a gas saturated environment. In addition, before the LSV test, more than 20 cycles of CV activation were performed to stabilize the curve. In the LSV test, the voltage scan range was 0.3 to -0.1 V (vs. RHE) and the scan rate was 5 mV s -1 The samples to be tested were respectively the nano high entropy phosphide / carbon composite material Nano-(Fe 0.30 Co 0.25Ni 0.25 Cu 0.10 Mo 0.10 )2P / C, the above-mentioned spare C, commercially available Pt / C, and the nano high entropy phosphide / carbon composite material Nano-(Fe 0.30 Co 0.25 Ni 0.25 Cu 0.10 Mo 0.10 )2P / C.
[0062] 3. Constant current charge and discharge cycle test: The sample was mixed with sublimed sulfur at a mass ratio of 1:3 and then reacted at 155°C for 12 hours. After cooling, conductive carbon black (Super-P) and polyvinylidene fluoride (PVDF) were added at a mass ratio of 8:1:1 and fully ground. Then N-methylpyrrolidone was added dropwise to form a slurry, which was coated on aluminum foil and vacuum dried and cut into discs with a diameter of 14 mm, which was the positive electrode (Nano-(Fe 0.30 Co 0.25 Ni 0.25 Cu 0.10 Mo 0.10 )2P / C@S or C@S), the assembled button cell was tested by constant current charge and discharge in the voltage window of 1.7-2.8V on the Xinwei battery test system. The tested samples were the nano high entropy phosphide / carbon composite material Nano-(Fe 0.30 Co 0.25 Ni 0.25 Cu 0.10 Mo 0.10 )2P / C, the above spare C.
[0063] The nano high entropy phosphide / carbon composite material Nano-(Fe 0.30 Co 0.25 Ni 0.25 Cu 0.10 Mo 0.10 )2P / C and the composite material prepared in Comparative Example 1 were subjected to scanning electron microscopy (SEM) and linear scanning voltammetry (LSV) tests. The nano high entropy phosphide / carbon composite material Nano-(Fe 0.30 Co 0.25 Ni 0.25 Cu 0.10 Mo 0.10 )2P / C was used as the cathode catalyst for lithium-sulfur batteries for electrochemical cycle testing and analysis, such as Figures 1 to 8 As shown:
[0064] Depend on Figure 1 The SEM spectrum of the nano high entropy phosphide particles Nano-(Fe0.30 Co 0.25 Ni 0.25 Cu 0.10 Mo 0.10 )2P is uniformly anchored in the hierarchical porous carbon.
[0065] Depend on Figure 2 From the EDS spectrum, we can see that the nano high entropy phosphide Nano-(Fe 0.30 Co 0.25 Ni 0.25 Cu 0.10 Mo 0.10 )2P, the six elements Fe, Co, Ni, Cu, Mo and P are evenly distributed in the nanoparticles without element segregation.
[0066] Depend on Figure 3 The S8 reduction linear sweep voltammetry (LSV) test shows that the nano high entropy phosphide Nano-(Fe 0.30 Co 0.25 Ni 0.25 Cu 0.10 Mo 0.10 )2P / C catalyst exhibits an earlier half-wave potential (E half-wave ) and a greater diffusion current intensity (J D ), showing its excellent catalytic performance.
[0067] Figure 4 The results show that the nano high entropy phosphide / carbon composite material Nano-(Fe 0.30 Co 0.25 Ni 0.25 Cu 0.10 Mo 0.10 )2P / C catalyst exhibits the best HER activity in 1 M KOH, requiring only 224 mV overpotential to reach 100 mA cm -2 , close to that of Pt / C catalyst, showing excellent electrocatalytic hydrogen evolution performance.
[0068] Figure 5 Constant current charge and discharge cycle test, Nano-(Fe 0.30 Co 0.25 Ni 0.25 Cu 0.10 Mo 0.10 )2P / C@S positive electrode assembled lithium-sulfur battery releases an initial discharge capacity of 1368mAh / g at a current density of 0.2C, and stably cycles 200 cycles with a capacity decay of 0.068% per cycle. The capacity decay of the lithium-sulfur battery assembled with C@S positive electrode is 0.15% per cycle. And it can be seen from the figure that Nano-(Fe 0.30 Co 0.25Ni 0.25 Cu 0.10 Mo 0.10 )2P / C@S exhibits higher coulombic efficiency and further indicates improved battery stability. These results indicate that Nano-(Fe 0.30 Co 0.25 Ni 0.25 Cu 0.10 Mo 0.10 )2P / C catalyst has high efficiency and stable catalytic activity.
[0069] Depend on Figure 6 The SEM spectrum of the nano high entropy phosphide particles Nano-(Fe 0.30 Co 0.25 Ni 0.25 Cu 0.10 Mo 0.10 )2P is anchored in the carbon matrix, which has less porous structure.
[0070] Depend on Figure 7 The LSV test shows that compared with Example 1, in which no alkaline substance is added, the nano high entropy phosphide Nano-(Fe 0.30 Co 0.25 Ni 0.25 Cu 0.10 Mo 0.10 )2P / C catalyst exhibits an earlier half-wave potential (E) than pure carbon in the electrocatalytic sulfur reduction reaction. half-wave ) and a greater diffusion current intensity (J D ), but compared with the addition of alkaline substances to Nano-(Fe 0.30 Co 0.25 Ni 0.25 Cu 0.10 Mo 0.10 )2P / C catalyst exhibits poor catalytic performance.
[0071] Depend on Figure 8 The HER linear sweep voltammetry (LSV) test shows that the nano high entropy phosphide Nano-(Fe 0.30 Co 0.25 Ni 0.25 Cu 0.10 Mo 0.10 )2P / C catalyst showed better activity than pure carbon in 1 M KOH, but required an overpotential of 300 mV to reach 100 mA cm -2 , the overpotential is larger than that when alkaline substances are added, and the catalytic activity is poor ( Figure 8 Pt / C was commercially available).
[0072] Table 1 is the analysis of the nano high entropy phosphide Nano-(Fe 0.30 Co 0.25 Ni 0.25 Cu 0.10 Mo 0.10 )The contents of metal elements Fe, Co, Ni, Cu, Mo and non-metallic element P in 2P. From the table, we can see that the atomic percentages of Fe, Co, Ni, Cu, Mo and P are 21.0%, 18.1%, 17.1%, 8.9%, 6.8% and 28.1% respectively.
[0073] Table 1 Example 1 Preparation of Nano High Entropy Phosphide Nano-(Fe 0.30 Co 0.25 Ni 0.25 Cu 0.10 Mo 0.10 )2P metal elements
[0074] element Content (at.%) Fe 21.0 Co 18.1 Ni 17.1 Cu 8.9 Mo 6.8 P 28.1
[0075] The foregoing description of specific exemplary embodiments of the present invention is for the purpose of illustration and demonstration. These descriptions are not intended to limit the present invention to the precise form disclosed, and it is clear that many changes and variations can be made based on the above teachings. The purpose of selecting and describing the exemplary embodiments is to explain the specific principles of the present invention and its practical application, so that those skilled in the art can realize and utilize various different exemplary embodiments of the present invention and various different selections and changes. The scope of the present invention is intended to be limited by the claims and their equivalents.
Claims
1. A nano high entropy phosphide / carbon composite material, characterized in that: The general formula of nano high entropy phosphide / carbon composite material is Nano-(Fe a Co b Ni c Cu d Mo e )2P / C, wherein the subscript value ranges are a is 0.25-0.3, b is 0.25, c is 0.25, d is 0.1-0.13, and e is 0.1-0.12; the nano high entropy phosphide / carbon composite material has efficient and stable catalytic performance.
2. The method for preparing the nano high entropy phosphide / carbon composite material according to claim 1, characterized in that: The following steps are included: (1) soaking the phosphorus-containing resin in an acid solution to adjust the pH of the phosphorus-containing resin, vacuum filtering, drying, and then crushing; (2) The phosphorus-containing resin obtained after pulverization in step (1) is added to water and stirred to obtain a mixture, and Fe salt, Co salt, Ni salt, Cu salt and Mo salt solutions are mixed evenly and added to the mixture, stirred, vacuum filtered and dried to obtain a precursor resin containing five elements of Fe, Co, Ni, Cu and Mo, denoted as M + Resin; (3) The M obtained in step (2) + The resin is added with alkaline substances and ground, and heat-treated under protective gas. After the reaction is completed, the resin is cooled, and the heat-treated substance is washed to neutrality and dried to obtain a nano high entropy phosphide / carbon composite material.
3. The method for preparing the nano high entropy phosphide / carbon composite material according to claim 1, characterized in that: The phosphorus-containing resin described in step (1) is LXP-P01 type resin. The acid solution described in step (1) is one of hydrochloric acid solution, nitric acid solution or acetic acid solution; the concentration of the acid solution is 0.5-2.5 mol / L.
4. The method for preparing the nano high entropy phosphide / carbon composite material according to claim 2, characterized in that: The pH value in step (1) is adjusted to 5-7; after vacuum filtration, the mixture is dried at 60° C. until the moisture content does not exceed 8% and then crushed.
5. The method for preparing the nano high entropy phosphide / carbon composite material according to claim 2, characterized in that: In step (2), 5 mL of water is added per gram of phosphorus-containing resin.
6. The method for preparing the nano high entropy phosphide / carbon composite material according to claim 2, characterized in that: The Fe salt, Co salt, Ni salt, Cu salt and Mo salt solutions described in step (2) are each added in an amount of 50 mL; the Fe salt is ferric chloride (FeCl3) with a concentration of 0.2 to 0.6 mol / L; the Co salt is cobalt chloride (CoCl2) with a concentration of 0.2 to 0.6 mol / L; the Ni salt is nickel chloride (NiCl2) with a concentration of 0.2 to 0.6 mol / L; the Cu salt is cupric chloride (CuCl2) with a concentration of 0.2 to 0.6 mol / L; and the Mo salt is molybdenum pentachloride (MoCl5) with a concentration of 0.2 to 0.6 mol / L.
7. The method for preparing the nano high entropy phosphide / carbon composite material according to claim 2, characterized in that: In step (2), the vacuum filtration is followed by complete drying at 60° C.; and the drying in step (3) is complete drying at 60° C.
8. The method for preparing the nano high entropy phosphide / carbon composite material according to claim 2, characterized in that: The stirring in step (2) is to maintain the temperature at 50-65° C., stir at a rate of 300 rpm, and stir for 3-6 hours.
9. The method for preparing the nano high entropy phosphide / carbon composite material according to claim 2, characterized in that: The alkaline substance in step (3) is one of potassium hydroxide or sodium hydroxide; the protective gas in step (3) is N2 or Ar atmosphere; the M in step (3) + The amount of resin added is 1 to 3 g; the M + The mass ratio of the resin to the alkaline substance is 1:0.05-0.
4.
10. The method for preparing the nano high entropy phosphide / carbon composite material according to claim 2, characterized in that: The heat treatment in step (3) is as follows: heating the temperature to 750-1050°C at a heating rate of 5-10°C / min and keeping the temperature for 1-3h.
Citation Information
Patent Citations
Nano transition metal phosphide-graphitized carbon composite material and one-step synthesis method thereof
CN103123970A
Three-dimensional porous carbon loaded nano high-entropy intermetallic compound composite material and preparation method thereof
CN116230884A
High-entropy metal alloy film and preparation method and application thereof
CN117051388A
High entropy composite oxide, manufacturing method thereof, and anode materials comprising the same
US20220135426A1
Multi-element compound nanoparticles, and systems and methods of making and use thereof
WO2022132883A1